Предмет:
МатематикаАвтор:
анонимРешение:
Возведем в квадрат обе части уравнения: sin(α) - cos(α) = 0,6.
(sin(α) - cos(α))^2 = 0,36 . Получаем:
sin(α)^2 + cos(α)^2 - 2 * sin(α) * cos(α) = 0,36.
Т.к. sin(α)^2 + cos(α)^2 = 1, то
2 * sin(α) * cos(α) = 1 - 0,36 = 0,64 и следовательно:
sin(α) * cos(α) = 0,64 / 2 = 0,32.
Ответ:
sin(α) * cos(α) = 0,32.
Автор:
camryn8xg1Добавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть